Charismatic Leadership Style to Overcome Employee Resistance to the Management of Organizational Change Process (Global Journal of Management and Business Research, 2022)
This study aims to propose a theoretical model to explore how charismatic leadership style can overcome the employee resistance to organisational change process. A qualitative method is used in a case study based on #x201C;Amman International Airport#x201D; where a charismatic leadership style is observed in defending the organization#x2019;s position in overcoming employee resistance against the chosen organizational change. The results suggest that charismatic leaders employ a set of coherent communication strategies in bringing up change in organisations and on the control of individuals and groups. Understanding the role of charismatic characteristics and features of leadership style gives us important insights into the role of the charismatic leader as well as his influence on his followers and their perceptions. Perhaps more importantly, it helps us understand how leaders can use, or at least take advantage of, organizational change processes and control of individuals and groups.
Keywords: charismatic leadership; employee resistance; followers; organisational change process; amman international airport